Marasmius magnus (Marasmiaceae, Basidiomycota) en Argentina - Ramírez, Natalia Andrea (2021)
Fil: Ramírez, Natalia Andrea. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.